2018
DOI: 10.5606/tftrd.2018.2314
|View full text |Cite
|
Sign up to set email alerts
|

Land- and pool-based intervention in female fibromyalgia patients: A randomized-controlled trial

Abstract: and pool-based intervention in female fibromyalgia patients: A randomized-controlled trial. Turk J Phys Med Rehab 2018;64(4):337-343. ABSTRACT Objectives:The aim of this study was to assess the effect of a standard physical rehabilitation intervention (SPRI) program, in pool-based (SPRI-P) and land-based (SPRI-L) environments, applied to female fibromyalgia (FM) patients with mild-to-moderate symptoms during a period of 20 weeks. Patients and methods:Between September 2016 and September 2017, a total of 73 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Figure 1 shows the PRISMA flow diagram along with reasons for exclusion, with common reasons being no description of exercise mechanisms, non-randomized trials, pain outcomes not reported, and mean differences not being significant. The type of exercise interventions investigated in the RCTs are as follows: aquatic exercise (17 trials), [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] aerobic exercise (12 trials), 14,25,[28][29][30][31][32][33][34][35][36][37][38][39] resistance exercise (13 trials), 15,21,31,35,[40][41][42][43][44][45][46][47][48] flexibility exercise (7 trials), 28,32,40,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 shows the PRISMA flow diagram along with reasons for exclusion, with common reasons being no description of exercise mechanisms, non-randomized trials, pain outcomes not reported, and mean differences not being significant. The type of exercise interventions investigated in the RCTs are as follows: aquatic exercise (17 trials), [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] aerobic exercise (12 trials), 14,25,[28][29][30][31][32][33][34][35][36][37][38][39] resistance exercise (13 trials), 15,21,31,35,[40][41][42][43][44][45][46][47][48] flexibility exercise (7 trials), 28,32,40,…”
Section: Resultsmentioning
confidence: 99%
“…The type of exercise interventions investigated in the RCTs are as follows: aquatic exercise (17 trials), [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] aerobic exercise (12 trials), 14,25,[28][29][30][31][32][33][34][35][36][37][38][39] resistance exercise (13 trials), 15,21,31,35,[40][41][42][43][44][45][46][47][48] flexibility exercise (7 trials), 28,32,40,41,43,45,49 Qigong (2 trials), …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read the article by Acosta-Gallego et al [1] published in your journal and congratulate the authors for conducting and reporting the findings of a longterm study (20 weeks) on the effects of pool versus land based physiotherapy interventions in female patients with fibromyalgia. However, we would like to offer the following commentary to contribute to the interpretation of the findings and be taken into consideration in the future studies on this topic.…”
mentioning
confidence: 99%